Budd-Chiari syndrome in a patient with ulcerative colitis. (22nd February 2018) - Bohra, Gopal Krishana; Chhabra, Vivek; Midha, Naresh; Sureka, Binit
Abstract : We report a case of 26-year-old man who was admitted on our ward for the evaluation of ascites. He was a known case of inflammatory bowel disease(ulcerative colitis) and was on regular mesalamine therapy. On evaluation, he was having high serum ascites albumin gradient. CT scan of the abdomen revealed features of portal hypertension and non-visualisation of right and middle hepatic veins along with thrombus in inferior vena cava, suggesting a diagnosis of Budd-Chiari syndrome (BCS). There are only few case reports available showing association of BCS with UC. Hence, we are reporting this interesting and rare case.